Changes in Blood Sugar Levels using Walking Excercise in the Elderly with Diabetes Mellitus (JONAH : Journal of Nursing and Homecare, 2025)
The elderly are an elderly group that is prone to experiencing various physical and mental changes, making them more susceptible to diseases, including diabetes mellitus (DM). DM is a chronic disease characterized by high blood sugar levels and can damage organs such as the heart, blood vessels, eyes, kidneys, and nerves. One way that can help lower blood sugar levels is through physical exercise such as walking. This study aims to determine the effect of walking exercise on blood sugar levels in elderly people with DM at PSTW in Pekanbaru. This study was descriptive with two subjects who routinely took metformin. The activity was carried out on June 3, 5, and 12, 2025 through observation and direct interviews. The results showed that after 30 minutes of walking exercise three times a week, the blood sugar levels of subject I decreased from 367 mg/dl to 233 mg/dl, and subject II from 172 mg/dl to 102 mg/dl. These results show that walking excercise can help lower blood sugar levels in elderly people with DM. Further research is suggested to involve more subjects, expand observations, and use more robust research designs such as experimental case studies.